Application of Thougt Stopping Therapy to Reduce Anxiety in Hypertension : Penarapan Terapi Thought Stopping Untuk Menurunkan Kecemasan Pada Klien Hipertensi (JURNAL UNEJ, 2023)
Hypertension is the most common cardiovascular disorder which is a major health challenge for people who experience hypertension. Anxiety due to negative thoughts that occur in hypertensive patients can affect treatment, emotions and sleep quality (Rosén et al., 2022). So there is a need for therapy that can help overcome negative thoughts, namely thought stopping, which is a therapy that aims to reduce anxiety, where the application of thought stopping therapy can help individuals to stop disturbing or threatening thoughts. Community service was carried out on July 22 2023, in Wonotoro Village. The methods used are lectures, direct discussions, video screenings, and interactive discussions about the benefits of herbal ingredients for health. The results obtained from this service are that the audience is enthusiastic about taking part in this intervention, the audience can also reduce negative thoughts that trigger hypertension. This therapy can be used as an alternative to lower blood pressure in hypertension sufferers who experience excessive anxiety. This technique is very easy for the general public to do.